Are obstetrical complications really involved in the etiology and course of schizophrenia and mood disorders?. (30th July 2016) - Buoli, Massimiliano; Bertino, Vincenzo; Caldiroli, Alice; Dobrea, Cristina; Serati, Marta; Ciappolino, Valentina; Altamura, A. Carlo
Abstract: The impact of stressful experiences during gestation or early life, leading to increased psychiatric disorders susceptibility, is currently well described in literature, however, few data are available on the association between obstetrical complications and later development of specific diagnoses or clinical features (e.g. psychotic symptoms). Aim of the present paper was to evaluate obstetrical complications frequency in different psychiatric diagnoses and their association with clinical features. Three hundred and eighty-eight patients with a diagnosis of schizophrenia, bipolar disorder or major depressive disorder were compared in terms of clinical presentation according to the presence, type and severity of obstetrical complications. Seventeen percent of the total sample (N=65) had history of at least one obstetrical complication. Patients with a history of at least one obstetrical complication result in an earlier age of onset (F=3.93, p=0.04) and a current higher GAF score (F=6.46, p=0.01). Lewis-Murray scale score was directly correlated with GAF scores (t=2.9, p=0.004) and inversely correlated with age at onset (t=−2.77, p=0.006). Obstetrical complications are frequently registered in patients with schizophrenia or mood disorders. In our sample, they appear to have an anticipatory effect on illness onset, but they seem not to be associated with a specific psychiatric diagnosis. Highlights: The association between obstetrical complications and psychiatric disorders has not been totally clarified. Patients with a history of at least one obstetrical complication seem to have an earlier age at onset. Obstetrical complications do not appear to be associated with specific diagnoses or psychotic symptoms. Obstetrical complications seem to have an anticipatory effect in patients with schizophrenia or a mood disorder.